Fundamental Change in the Nature of Chemical Bonding by Isotopic Substitution1. Issue 50 (10th October 2014) - Fleming, Donald G.; Manz, Jörn; Sato, Kazuma; Takayanagi, Toshiyuki
Abstract Isotope effects are important in the making and breaking of chemical bonds in chemical reactivity. Here we report on a new discovery, that isotopic substitution can fundamentally alter the nature of chemical bonding. This is established by systematic, rigorous quantum chemistry calculations of the isotopomers BrLBr, where L is an isotope of hydrogen. All the heavier isotopomers of BrHBr, BrDBr, BrTBr, and Br4HBr, the latter indicating the muonic He atom, the heaviest isotope of H, can only be stabilized as van der Waals bound states. In contrast, the lightest isotopomer, BrMuBr, with Mu the muonium atom, alone exhibits vibrational bonding, in accord with its possible observation in a recent experiment on the Mu+Br2 reaction. Accordingly, BrMuBr is stabilized at the saddle point of the potential energy surface due to a net decrease in vibrational zero point energy that overcompensates the increase in potential energy.